A review of chemotherapeutic drugs-induced arrhythmia and potential intervention with traditional Chinese medicines - Li, Weina; Cheng, Xiaozhen; Zhu, Guanghui; Hu, Ying; Wang, Yunhan; Niu, Yueyue; Li, Hongping; Aierken, Aikeremu; Li, Jie; Feng, Ling; Liu, Guifang (Frontiers in Pharmacology, 2024)
Significant advances in chemotherapy drugs have reduced mortality in patients with malignant tumors. However, chemotherapy-related cardiotoxicity increases the morbidity and mortality of patients, and has become the second leading cause of death after tumor recurrence, which has received more and more attention in recent years. Arrhythmia is one of the common types of chemotherapy-induced cardiotoxicity, and has become a new risk related to chemotherapy treatment, which seriously affects the therapeutic outcome in patients. Traditional Chinese medicine has experienced thousands of years of clinical practice in China, and has accumulated a wealth of medical theories and treatment formulas, which has unique advantages in the prevention and treatment of malignant diseases. Traditional Chinese medicine may reduce the arrhythmic toxicity caused by chemotherapy without affecting the anti-cancer effect. This paper mainly discussed the types and pathogenesis of secondary chemotherapeutic drug-induced arrhythmia (CDIA), and summarized the studies on Chinese medicine compounds, Chinese medicine Combination Formula and Chinese medicine injection that may be beneficial in intervention with secondary CDIA including atrial fibrillation, ventricular arrhythmia and sinus bradycardia, in order to provide reference for clinical prevention and treatment of chemotherapy-induced arrhythmias.